Electronics and Nuclear Physics - Duncan, T., BSc M Inst P. (London, 1979)
Atomic nature of matter and electricity, The electron, Cathode ray oscilloscope, Rectification, Amplification, Radio: oscillation: detection, Photoelectric emission, X-rays, Conduction in gases: positive ray: isotopes, Radioactivity...